2017
DOI: 10.1103/physrevb.96.157101
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Evidence of a first-order phase transition to metallic hydrogen”

Abstract: A recent paper by Zaghoo et al. 1 presents optical data at high-pressure and high-temperature and interprets the data as evidence for a first-order phase transition to metallic hydrogen during heating. Here we argue that the presented data are contradictory with these claims. Elucidating this issue is important for building a coherent picture that is emerging as the results of theoretical calculations of various levels 2-4 and experimental investigations employing static and dynamic compression techniques 5,6… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
0
12
1
Order By: Relevance
“…The results presented here clearly demonstrate the existence of two transformation boundaries corresponding to the formation of absorptive and reflecting hydrogen (Figure ). The one at lower P–T conditions has been established in dynamic and DAC experiments . It has been suggested that this boundary is related to a bandgap closure, rather than the plasma transition.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The results presented here clearly demonstrate the existence of two transformation boundaries corresponding to the formation of absorptive and reflecting hydrogen (Figure ). The one at lower P–T conditions has been established in dynamic and DAC experiments . It has been suggested that this boundary is related to a bandgap closure, rather than the plasma transition.…”
Section: Discussionmentioning
confidence: 87%
“…Transient reflectance signal in this regime shows a small, spectrally independent increase (Figure S3, Supporting Information) which can be explained by a small change in the refractive index of H 2 (D 2 ) correlated with bandgap reduction . In this regime, peak temperature measured radiometrically (Figure S4, Supporting Information) tends to increase slowly with laser power, while the duration at which the sample remains hot (and thus emits) increases (Figure S5, Supporting Information); temperature increases more rapidly at higher laser power.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper we have used the proper geometry and thermodynamic properties for the experimental demonstration of LMH [16,17], whereas earlier simulations are not relevant to this experiment [19][20][21]. We have found that the results of the simulation are quite sensitive to material properties such as thermal conductivity (TC) and latent heat, but also the optical properties of all materials in the DAC, as these play a large role in determining the absorbed laser power.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the heating curve relating temperature to applied laser power is accompanied by the appearance of a plateau, indicating the presence of latent heat of transition. Several authors [15,[18][19][20] interpreted the plateau differently, instead relating it to a continuous change in optical parameters due to temperature dependent bandgap closure.…”
Section: Introductionmentioning
confidence: 99%